Alto de las nubes: propuesta arquitectónica para un ecohotel (Baraya, Huila) (2020)
The research aims at the architectural design of the Ecohotel Alto de las nubes located in the municipality of Baraya belonging to the Department of Huila, the document exposes the problem of ignorance of the natural wealth of the cloud lagoon and the loss of Opportunities for the positioning of ecotourism, through the systematization of the questions, the solution strategies are generated to boost knowledge, landscape wealth, attention and visit of neighboring inhabitants and tourists to the body of water. The purpose of the intervention is to boost the stay in the place and propose ecotourism as a plan to improve the economic development of the territory, the project is aimed at local people, the department and the rest of the country whose interest are activities carried out in a natural environment. In addition, the research frames the historical context that characterizes ecotourism activity in various parts of the world and the reference of projects that have contemplated the chosen theme. Finally, the study is based on a methodology of analysis of economic, environmental, cultural and social components divided into: Area that has direct influence on the project being this the municipality of Baraya (rural area), then the intervention area is analyzed, between the paths: El Cañón and Centro Poblado El Hotel. The following scale of study contains the intervention polygon, defined by limits that condense the chosen lot together with the urban intervention of the project.